PENDAPAT FUQAHA TENTANG KHIYAR DALAM JUAL BELI: PENDAPAT FUQAHA TENTANG KHIYAR DALAM JUAL BELI - Ahmad Rifai (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2022)
In a sale transaction, the buyer, as the person who enters into a sales contract with the seller, has the option of continuing or terminating the sales contract for the goods purchased. According to fiqh scholars, Islam regulates or allows the use of khiyar for the benefit of all parties in a transaction when there is an urgent need. The aim of this study was to find out how the fuqaha perceived khiyar in terms of buying and selling. The author's research method is a literature study that collects data through data collection, and the four priests of the institution classify khiyar similarly. The four madhhab priests accept khiyar terms and shame khiyar in buying and selling. The priests of the madhhab disagree on the legitimacy of the khiyar. Some agree it's okay, while others don't